The Effect of Video Camera, Microphone and Chat Box Use on Social Presence and Engagement in an Online Group Activity - Minosky, Shayna; El Aini, Nachwa; Justus, Brandon; Bali, Tanisha (Online Learning, 2024)
With the rapidly expanding availability of online courses, concerns have been raised about student engagement and connection within the online environment. Using an experimental design, we examined the effects of video camera, microphone, and chat box communication mediums on students’ experiences of social presence, peer rapport, motivation, satisfaction, and anxiety. A total of 133 undergraduate students were randomly assigned to a video, audio, or chat box condition and asked to complete an online interactive group task and a post-task survey. One-ways ANOVAs indicated that participants in the chat box condition reported lower levels of social presence, peer rapport, motivation and satisfaction compared to both the video and audio conditions, with no differences between the video and audio conditions. Those in the video condition reported higher anxiety levels than those in the chat box condition. We recommend that students participate in their online classes using video cameras and/or microphones to increase engagement and interpersonal connections with peers.